Response of Chickpea (Cicer Arietinum L.) to Gypsum and Phosphorus Application in Sodic Soil - Yadav, H D; Yadav, O P; Dhankar, O P; Kumar, Virender (Annals of Arid Zone, 2016)
In a pot experiment 01) a ameliorated sodic loamy sand soil, the response of chickpea was observed as a function of levels of phosphorus (0,20,40 and 60 kg P205/ha). The soil ameliorated with gypsum upto 50% G.R. of soil showed increase in grain yield and other growth parameters igermination and nodulation) significantly and decrease in the pH and ESP to 8.1 and 12 (below - critical level) from 9.6 and 42 of control, respectively. Phosphorus application only upto 40 kg P205/ha) increased the grain yield significantly.